Body size-dependent energy storage causes Kleiber’s law scaling of the metabolic rate in planarians - Thommen, Albert; Werner, Steffen; Frank, Olga; Philipp, Jenny; Knittelfelder, Oskar; Quek, Yihui; Fahmy, Karim; Shevchenko, Andrej; Friedrich, Benjamin M; Jülicher, Frank; Rink, Jochen C (eLife, 2019)
Kleiber’s law, or the 3/4 -power law scaling of the metabolic rate with body mass, is considered one of the few quantitative laws in biology, yet its physiological basis remains unknown. Here, we report Kleiber’s law scaling in the planarian Schmidtea mediterranea. Its reversible and life history-independent changes in adult body mass over 3 orders of magnitude reveal that Kleiber’s law does not emerge from the size-dependent decrease in cellular metabolic rate, but from a size-dependent increase in mass per cell. Through a combination of experiment and theoretical analysis of the organismal energy balance, we further show that the mass allometry is caused by body size dependent energy storage. Our results reveal the physiological origins of Kleiber’s law in planarians and have general implications for understanding a fundamental scaling law in biology.
Keywords: Kleiber's law; 3/4-power law; metabolic rate; metabolic scaling; energy metabolism; planaria